2‐Ethyl‐1‐[5‐(4‐methylphenyl)pyrazol‐3‐yl]‐3‐(thiophene‐2‐carbonyl)isothiourea: molecular ribbons containing three types of hydrogen‐bonded ring. Issue 11 (16th October 2014) - Castro, Edison; Insuasty, Henry; Insuasty, Braulio; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> The title compound, C18H18N4OS2, was prepared by reaction of S, S‐diethyl 2‐thenoylimidodithiocarbonate with 5‐amino‐3‐(4‐methylphenyl)‐1H‐pyrazole using microwave irradiation under solvent‐free conditions. In the molecule, the thiophene unit is disordered over two sets of atomic sites, with occupancies of 0.814 (4) and 0.186 (4), and the bonded distances provide evidence for polarization in the acylthiourea fragment and for aromatic type delocalization in the pyrazole ring. An intramolecular N—H...O hydrogen bond is present, forming an S(6) motif, and molecules are linked by N—H...O and N—H...N hydrogen bonds to form a ribbon in which centrosymmetric R22(4) rings, built from N—H...O hydrogen bonds and flanked by inversion‐related pairs of S(6) rings, alternate with centrosymmetric R22(6) rings built from N—H...N hydrogen bonds.